Sonochemical preparation of alumina-spheres loaded with Pd nanoparticles for 2-butyne-1, 4-diol semi-hydrogenation in a continuous flow microwave reactor. Issue 13 (13th February 2018) - Calcio Gaudino, Emanuela; Manzoli, Maela; Carnaroglio, Diego; Wu, Zhilin; Grillo, Giorgio; Rotolo, Laura; Medlock, Jonathan; Bonrath, Werner; Cravotto, Giancarlo
Abstract : A novel protocol for microwave-assisted alkyne semi-hydrogenation under heterogeneous catalysis in a continuous flow reactor is reported herein. Abstract : A novel protocol for microwave-assisted alkyne semi-hydrogenation under heterogeneous catalysis in a continuous flow reactor is reported herein. This challenging task has been accomplished using a multifaceted strategy which includes the ultrasound-assisted preparation of Pd nanoparticles (average Ø 3.0 ± 0.5 nm) that were synthesized on the μ-metric pores of sintered alumina spheres ( Ø 0.8 mm) and a continuous flow reaction under H2 (flow rate 7.5 mL min −1 ) in a microwave reactor (counter-pressure 4.5 bar). The semi-hydrogenation of 2-butyne-1, 4-diol in ethanol was chosen as a model reaction for the purposes of optimization. The high catalyst efficiency of the process, in spite of the low Pd loading (Pd content 111.15 mg kg −1 from ICP-MS), is due to the pivotal role of ultrasound in generating a regular distribution of Pd nanoparticles across the entire support surface. Ultrasound promotes the nucleation, rather than the growth, of crystalline Pd nanoparticles and does so within a particularly narrow Gaussian size distribution. High conversion (>90.5%) and selectivity to ( Z )-2-butene-1, 4-diol (95.20%) have been achieved at an alkyne solution flow rate of 10 mL min −1 . The lead-free, alumina-stabilized Pd catalyst was fully characterized by TEM, HR-TEM, EDX, IR, XRPD and AAS. Highly dispersed Pd nanoparticles have proven themselves to be stable under the reaction conditions employed. The application of the method is subject to the dielectric properties of substrates and solvents, and is therefore hardly applicable to apolar alkynes. Considering the small volume of the reaction chamber, microwave-assisted flow hydrogenation has proven itself to be a safe procedure and one that is suitable for further scaling up to industrial application.